Legal Analysis of AI-Generated Creations: Copyright Law Perspectives - Praja Chrisna Bagus Edhita; Hakim Hary Abdul; Basri; Kurniaty Yulia; Sari Elvira Purnama (E3S Web of Conferences)
The development of Artificial Intelligence (AI) in digital transformation has a significant impact on people's lives. AI is able to solve complex problems with high accuracy to produce a creation. This raises problems and negative impacts related to copyright. The absence of explicit rules governing the creation of AI leads to legal uncertainty. The 2014 copyright law does not fully cover AI-generated works. Legal analysis shows that AI is just a computer programming tool that performs tasks based on human commands. AI uses algorithms and computer training for recognition, prediction, and decision-making. This research aims to analyze the legal position of AI and the legal status of creations generated by AI. While legal consequences the creator or user of AI is legally responsible when AI infringes the copyrights of others. This study uses qualitative research methods with the approach of legislation and concepts. This study concluded that AI has a role as a producer of creation and innovation. However, AI is not a subject of law, and the legal consequences of works produced by AI depend on the legal responsibilities of the creators or users of the relevant AI.